Human pregnancy is accompanied by modifications in B cell development and immunoglobulin profile. (September 2018) - Ziegler, K.B.; Muzzio, D.O.; Matzner, F.; Bommer, I.; Ventimiglia, M.S.; Malinowsky, K.; Ehrhardt, J.; Zygmunt, M.; Jensen, F.
Highlights: The results presented here shed light on how B-lymphocytes behave during human pregnancy. In addition, our results reinforce the hypothesis of human pregnancy being a Th2-humoral associated process. And highlight the importance of natural antibodies as key immunoglobulin during normal pregnancies. Abstract: Though human pregnancy success has been classically linked with a shift into a Th2 immunoglobulin producing cell response, a clear picture concerning B cell development and immunoglobulin profile during human pregnancy is missing. We analyzed in this work the dynamic of different B cell populations in peripheral blood of pregnant women on the first, second and third trimester of pregnancy. As control, age-matched non-pregnant fertile women were included. Additionally, we quantified the levels of immunoglobulin (IgG1, IgG2, IgG3, IgG4, IgM, IgA and IgE) in the serum of pregnant and non-pregnant women. We observed a significant decrease in the percentages of transitional B cells in peripheral blood of pregnant women as compared to non-pregnant control women. Besides, percentages of naïve as well as switched and non-switched memory B cells in peripheral blood of pregnant women were similar to those in non-pregnant control women. Interestingly, although we did not observe differences in the activation status of B cells as well as in the percentages of plasma cells between pregnant and non-pregnant women, we observed significantly higher levels of IgM, IgA, IgG3, more likely natural antibodies, as well IgG4 in serum of pregnant women compared to non-pregnant age matched control women.